The strategy for fulfilling restitution payments for victims of human trafficking criminal acts - Sitompul, Rina Melati; Mulyadi, Mahmud; Ekaputra, Mohammad; Danil, Elwi (Edelweiss Applied Science and Technology, 2025)
The right of every citizen to obtain equality and status before the law, as well as the fulfillment and acquisition of their rights. Restitution is compensation for victim assistance, as a fundamental right of law enforcement for human trafficking crimes, and mandatory provisions to be fulfilled by perpetrators for the consequences of the criminal acts committed. Since Law No. 21 of 2007 was enacted, the fulfillment of victims’ rights has not been optimally implemented or facilitated at all. Previous research found two decisions at the Medan District Court; until now, the payment order has had no meaning for the convict, thus causing neglect and disregard for the rights that the victim has expected. The finding of this failure to pay, when associated with the calculation of losses concluded by the Witness Victim Protection Agency, between the amount concluded, the amount decided by the judge, and the amount of the perpetrator’s ability to pay, has a considerable gap. It proves the opportunity for this criminal decision to be set aside. Based on these findings, it is necessary to conduct a study to improve the strategy for achieving the intended justice. This study is legal research conducted through a case approach and legal concepts; the aim is to find solutions to the evaluation process using existing legal regulations.